2007
DOI: 10.1080/10428190601059753
|View full text |Cite
|
Sign up to set email alerts
|

Relevant prognostic features of multiple myeloma and the new International Staging System

Abstract: The new International Staging System should be reported in all future studies of multiple myeloma. However, the system fails to account for recent research findings pertaining to mechanisms of disease progression. This review describes development of the International Staging System and details prognostic factors that may further our understanding of the biology of multiple myeloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Based on the ISS, the median survival of patients with stage I, II, or III disease is estimated at 62, 44, and 29 months, respectively 6. Although serum β 2 -microglobulin and albumin levels combine in the ISS to provide a powerful prognostic tool, a number of independent prognostic markers have been described that may further assist in predicting outcome 17. Many established prognostic markers allowing identification of high-risk patients early in the disease course have been derived from studies of conventional chemotherapy and include age, β 2 -microglobulin level, World Health Organization (WHO) performance status, serum calcium, interleukin-6 (IL-6) level, bone marrow plasma cell labeling index, and morphological features 18,19.…”
Section: Disease Overviewmentioning
confidence: 99%
“…Based on the ISS, the median survival of patients with stage I, II, or III disease is estimated at 62, 44, and 29 months, respectively 6. Although serum β 2 -microglobulin and albumin levels combine in the ISS to provide a powerful prognostic tool, a number of independent prognostic markers have been described that may further assist in predicting outcome 17. Many established prognostic markers allowing identification of high-risk patients early in the disease course have been derived from studies of conventional chemotherapy and include age, β 2 -microglobulin level, World Health Organization (WHO) performance status, serum calcium, interleukin-6 (IL-6) level, bone marrow plasma cell labeling index, and morphological features 18,19.…”
Section: Disease Overviewmentioning
confidence: 99%
“…Clinical and biochemical staging systems are used to assess patients with MM at presentation; but as the underlying disease differs in each individual,7 molecular cytogenetic prognostic indicators are increasingly important for stratifying patients into risk categories for individualised treatment 8 9. Karyotype and fluorescence in situ hybridization (FISH) analyses have been used to investigate these molecular cytogenetics prognostic factors, but more readily available, robust and inexpensive technologies would have clinical utility and facilitate exploration of the functional basis of a patient’s disease 10…”
mentioning
confidence: 99%
“…PET/CT could be done in place of MR imaging, because it has been shown that a normal PET/ CT reliably predicted stable MGUS in a study of 98 patients. 13 Likewise, patients with the generalized form of myeloma should only have a generalized decrease in bone mineral density (often documented by bone densitometry) without discrete focal lytic lesions. If focal lesions are found, these patients should be placed in the category of typical multiple myeloma.…”
Section: Imaging Workupmentioning
confidence: 99%
“…25 Complete response by MR imaging is predictive of better outcome and is more meaningful than response of laboratory values. 13 Response of spine disease on MR imaging is best determined using the bone marrow evolution index described by Lecouvet et al (Table 4). 26 Findings related to the number and size of lesions are combined with changes in lesion enhancement and the bone marrow background to determine improved, stable, or worsening disease status.…”
Section: Update On Imaging Techniquesmentioning
confidence: 99%